Faktor-Faktor Yang Mempengaruhi Minat Usahatani Bawang Merah Di Dataran Tinggi (Desa Bandorasa Kulon Kecamatan Cilimus Kabupaten Kuningan) - Sukaesih; Yayat Rahmat Hidayat; R. Eviyati (Paradigma Agribisnis, 2024)
Shallots have many benefits for human life, especially as one of the food flavoring seasonings consumed by the people of Indonesia. Along with the increase in population, the need for shallots has increased, motivating farmers to increase shallot production in Bandorasa Kulon Village. This study aims to (1) determine the condition of land suitability, availability of production inputs, market potential and experience of shallot farming in Bandorasa Kulon Village (2) determine the influence of land suitability, availability of production inputs, market potential and farming experience on the interest of shallot farming in Bandorasa Kulon Village. This method and type of research uses descriptive quantitative methods with survey approach techniques. The data analysis used is multiple linear regression analysis. The samples in this study were as many as 55 shallot farmers. The results showed that (1) the land suitability variabel was in the “very suitable” category, the availability of production inpits was in the “available” category, the market potential variabel was in the “very likely” category, the farming experienced variabel was in the interest variabel was in the “experienced” category, and interest variabels in the category “highly interested” (2) Land suitability, availability of production inputs, market potential and experience together affect the interest of shallot farming in Bandorasa Kulon Village while farming experience has a negative effect.Keywords: Shallots, farming interests